Supositio, conotatio e signicatio: A crítica do nominalismo ockhamiano ao realismo - Brito, Marcéu gautama Soterorudá (2011)
This study aims to investigate how is the critique of nominalist system ockhamiano front of realistic theories developed in the Middle Ages. For this research takes place we choose to trace an investigative path that begins with the elucidation of what the 'Quarrel of the Universal' in the Middle Ages and the establishment of typologies that bring together the theories of the period. Later we work with the contextualization of the logical system developed by William of Ockham setting the bases of your system and pointing out some of the realistic writers who are criticized by the author. So that the logic of the author system became clear we seek to elucidate the logic of the terms of their time, which means the author's nominalism and what are the logical tools that he used to implement his critique of realism, namely: the supposition, the connotation and the signification. Finally we seek to discuss and demonstrate what the nominalist response of the author face the realistic theoretical models, placing the universal only with mental existence, exerting a semantic function, and devoid of ontology and a reality that is outside the human mind, shifting the axis the discussion of the problem to the field of logic to the detriment of the ontological field.